THE EVOLUTION OF PHOTOGRAPHY IN MOTION - Радомський, Олександр (SWorldJournal, 2024)
The article focuses on the evolution of motion photography. The aim of the study is to explore the unique techniques and styles used to capture the dynamics of moments in photography. General scientific methods of cognition, such as analysis, synthesis, c